A Comprehensive Review on Piles (Homoeopathy for All, 2025)
The term “Piles” has originated  from the Latin word “pila”, meaning  “a ball”. Clinically termed as  Hemorrhoids, it refers to a condition  which involves the formation of  swollen, enlarged veins in the anus  and the lower rectum. Although the  presence of hemorrhoidal veins in  the anal canal is a normal anatomical  feature, they are referred to as Piles  when they become inflamed, leading  to pain, discomfort, itching or  bleeding. There are different types  of Piles namely external (beneath  the skin around the anus), internal  (within the rectum), prolapsed  (protruding outside the anus) and  thrombosed (containing a blood clot  within an external hemorrhoid).
Keywords: hemorrhoidal veins; discomfort; Piles primarily; digital rectal examination